Leisure, pleasure, and healing : spa culture and medicine in ancient eastern Mediterranean - Dvorjetski, Esti. (Supplements to the Journal for the study of Judaism ;, 2007)
The book deals with leisure, pleasure and healing at the thermo-mineral sites in the Levant since the biblical era throughout the Hellenistic, Roman, Byzantine, and early Muslim periods. It looks closely at the question of whether the spas, which are models for social interaction between pagans, Christians and Jews, served as sacred cult places or popular sites of healing. The main objectives of the book are as follows: • Clarifying the leisure-time activities at the spas based on Classical and Rabbinic literature, pilgrims' travel-books, Syriac and Arabic texts, the Geniza fragments, cartographic evidence, and archaeological findings. • Lightening the daily life, healing cults, medical recommendations and treatments. • Examining the social history of medicine at the curative baths.